A Combination of Two Probiotics, Lactobacillus sporogenes and Clostridium butyricum, Inhibits Colon Cancer Development: An In Vitro Study - Oana Budu; Christian Banciu; Iulia Pinzaru; Cristian Sarău; Daniel Lighezan; Codruța Șoica; Cristina Dehelean; George Drăghici; Alina Dolghi; Alexandra Prodea; Marius Mioc (Microorganisms, 2022)
Cancer remains a leading cause of death worldwide and, even though several advances have been made in terms of specific treatment, the late-stage detection and the associated side effects of the conventional drugs sustain the search for better treatment alternatives. Probiotics are live microorganisms that have been proven to possess numerous health benefits for human hosts, including anticancer effects. In the present study, the in vitro effect of the association of two probiotic strains (PBT), Lactobacillus sporogenes and Clostridium butyricum, were tested against colon (HT-29 and HCT 116), lung (A549), and liver (HepG2) cancer cell lines, alone or in combination with 5-fluorouracil (5FU). Moreover, the underlying mechanism of PBT and PBT-5FU against the HT-29 cell line was evaluated using the Hoechst 33342 staining, revealing characteristic apoptotic modifications, such as chromatin condensation, nuclear fragmentation, and membrane blebbing. Furthermore, the increase in the expression of pro-apoptotic Bax, Bid, Bad, and Bak proteins and the inhibition of the anti-apoptotic Bcl-2 and Bcl-XL proteins were recorded. Collectively, these findings suggest that the two strains of probiotic bacteria, alone or in association with 5FU, induce apoptosis in colon cancer cells and may serve as a potential anticancer treatment.